ANALISIS PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN KOTA BARU KOTA JAMBI - Mariady . (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
The purpose of this study is to determine the effect of leadership and work environment on employee performance. Research is conducted at Kota Baru District Jambi City, respondents is 55 employees. The results show that leadership and work environment are simultaneously have positive and significant effect on employee performance. leadership and work environment influence of on employee performance is partially positive and significant. However, leaders need to monitor and evaluate work activities of employees, directing and empowering employees to manage the administration of rewards and sanctions as well or provide / budgeted labor facilities or equipment that can improve employee job performance in compliance with the Civil Service.Keywords : Leadership, work environment, employee performance, partisipative survey and Kota Baru distrik Jambi city